Computational screening of metal–organic frameworks for biogas purification. Issue 6 (15th October 2019) - Demir, Hakan; Cramer, Christopher J.; Siepmann, J. Ilja
Abstract : A hierarchical screening process is used to find a potentially top-performing metal–organic framework for biogas purification. Abstract : Biogas, which involves methane as the combustible compound, is an abundant and renewable energy resource that produces less harmful gases than conventional fossil-based liquid and solid energy sources. Although biogas is of primary interest due to its methane content, it may also include other gases, such as CO2, N2, H2 S, and NH3 . Studies investigating biogas purification often assume that biogas is a binary 50%/50% mixture of methane and carbon dioxide. However, together with N2, the toxic contaminants, H2 S and NH3 should be accounted for in the biogas mixture for a more realistic separation application. In this study, the computation-ready experimental metal–organic framework (CoRE-MOF) database is screened to identify a shortlist of potentially high-performing MOFs for multi-component biogas purification. Our hierarchical screening process involves (i) removal of MOFs with sub-3 Å pore limiting diameter and uncommon metal nodes, (ii) removal of MOFs that do not selectively capture the four undesired compounds, as determined from grand canonical Monte Carlo (GCMC) simulations for the binary mixtures of CH4 /(CO2 or N2 or H2 S or NH3 ), and (iii) ranking of the remaining structures based on various performance metrics determined from GCMC for a five-component mixture. Finally, the relations between some of these metrics and structural properties are discussed to reveal favorable structural characteristics for biogas upgrading.